Spatial distribution and temporal variation of nitrate nitrogen and oxygen isotopes in the upper equatorial Pacific Ocean. (6th November 2015) - Rafter, Patrick A.; Sigman, Daniel M.
Abstract: Equatorial Pacific nitrate 15 N/ 14 N and 18 O/ 16 O ( δ 15 N and δ 18 O) measurements from repeat station occupations are used to: (1) identify the source of surface waters, (2) estimate the nitrate assimilation isotope effect, (3) characterize the temporal relationship between the supply and consumption of nitrate in surface waters, and (4) quantify the degree of nitrate consumption in nitrate‐bearing surface waters. Surface nitrate assimilation was consistent with consumption of a closed nitrate pool at 63–80% of stations. Those stations yielded nitrate assimilation isotope effects of 6.0‰ ± 0.4‰ for N and 5.9‰ ± 0.6‰ for O, with an N:O isotope effect ratio of 1.0 ± 0.1, consistent with nitrate consumption being the dominant biogeochemical flux in the euphotic zone. The euphotic zone data point to the local Equatorial Under Current as the dominant source of surface nitrate along the equator, although surface waters at 110°W and ≥5° south of the equator show signs of surface nitrate input from further east. The collected findings suggest that nitrate delivery along the equatorial Pacific is dominated by Ekman upwelling rather than surface advection or vertical or lateral mixing. Surface nitrate δ 15 N and δ 18 O are correlated with seasonality and El Niño‐Southern Oscillation, with the implied degree of surface ocean nitrate consumption decreasing with increased upwelling strength. Incomplete consumption of surface nitrate near the equator lowers the δ 15 N of subsurface equatorial "thermostad" nitrate through the remineralization of low δ 15 N sinking organic matter while the continued consumption of the residual surface nitrate transported away from the equator raises the nitrate δ 15 N in off‐equatorial subsurface waters.